The Sociology of Religion: A Comparison of the Thinking of Emile Durkheim and Max Weber in Understanding the Role of Religion in Modern Society - Ulfain Ulfain; Toat Haryanto; Mubarok Fatahillah; Husnul Hafidhoh (Jurnal Indonesia Sosial Teknologi, 2026)
The background of this research focuses on the importance of understanding the role of religion in modern society, particularly through the thoughts of two major figures in the sociology of religion, Max Weber and Émile Durkheim. Although both agree that religion influences social structures, their views on its role differ significantly. The purpose of this study is to compare the thoughts of Max Weber and Émile Durkheim regarding the role of religion in modern society. The methodology used in this study is a qualitative approach with literature analysis, in which data are collected through the examination of works related to the theories of Weber and Durkheim, as well as relevant previous studies. The results show that Weber emphasized the role of religion in the formation of capitalism, while Durkheim focused on its role in creating social solidarity. Although they approach the issue in different ways, both agree that religion has a significant influence on the formation and organization of society. This research contributes to enriching the study of the sociology of religion by offering a new perspective for understanding the dynamics of religion in an increasingly complex and pluralistic modern society